PENGARUH BRAIN GYM TERHADAP TEKANAN DARAH PADA ORANG DENGAN HIPERTENSI DI RW 13 GIWANGAN UMBULHARJO YOGYAKARTA - Pratama, Antonius Yogi; Listyaningsih, Enik (STIKES Bethesda Yakkum, 2020)
ABSTRACT Background: Hypertension is still a major public health problem and a leading cause of death in the world. High blood pressure can be prevented by practicing a healthy lifestyle and treating the disease with medication. Apart from the use of drugs, complementary therapy is needed to control hypertension, such as Brain Gym. Objective: To determine the effect of Brain Gym on systolic and diastolic blood pressure in people with hypertension. Method: researchers used a quasi-experimental design with the One Group Pretest - Postest Design without a control group. T-test analysis was applied to investigate its mean differences between blood pressure before and after doing Brain Gym. Results: there was an average difference between pre and post at systolic pressure of 3,913 mmHg, t arithmetic (2,510)> t table (2.04) and p.value (0.02) <? (0.05). As for the diastolic pressure of 2.783 mmHg, t arithmetic (2.222)> t table (2.04) and p.value (0.036) <? (0.05). Conclusion: There is an effect of Brain Gym toward blood pressure in Hypertension Patients. Suggestion: Hypertension Patients in RW 13 Desa Giwangan are suggested to do Brain Gym as an alternative therapy to reduce blood pressure. Keywords: brain gym, hypertension, hypertension management